A Study of Translation Problems and Translation Editing of the Thai Literary Work “Behind The Picture”: การศึกษาปัญหาการแปลและการปรับบทแปลวรรณกรรมไทยเรื่อง “ข้างหลังภาพ” - Painarin, Manus; Tipayasuparat, Nakonthep (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2022)
This research aims to investigate translation problems and translation editing techniques of the Thai literary novel “Behind The Picture”, written by Sriburapa (1973)and translated into the English language by Marcel Barang (1936). The framework was adopted from the translation editing techniques created by Chaweang Chantaket (1985), Mona Baker (1992), and Sanchwi Saibua (1999), and the purposive sampling was employed. Forty samples from 20 chapters were collected through the analysis of three levels: sound and orthographical, lexical, and syntactic levels. The results revealed that, in terms of the sound and orthographical level, the most frequently employed technique was structure of words (10.30 %), and the least found was sound (9.27 %). As for the lexical level, the most found technique was using a more neutral or less expressive word (10.30 %), and the least found were using a loanword or a loanword plus explanation (0.51 %) and cultural substitution (0.51 %). For the syntactic level, the most found technique was changing sentences to phrases and vice versa (17.52 %), and the least found were paraphrasing using a related word (0.51 %) and adding or cutting words (0.51 %). In addition, the results disclosed that most of the techniques belonged to the literal and free translation and reflected that most translation problems originated from cultural differences that could be handled with different translation editing techniques. บทคัดย่อ บทความวิจัยฉบับนี้มีวัตถุประสงค์เพื่อศึกษาเกี่ยวกับปัญหาการแปลและการปรับบทแปลวรรณกรรมไทยเรื่อง “ข้างหลังภาพ” ประพันธ์โดย ศรีบูรพา (2479) และแปลเป็นภาษาอังกฤษโดย มาร์เซล บารัง (1936) ผู้วิจัยนำหลักเกณฑ์และกลวิธีในการปรับบทแปลของ เชวง จันทเขต (1985) โมนา เบเกอร์ (1992) และสัญฉวี สายบัว (1999) ใช้เป็นกรอบในการวิเคราะห์และยังเป็นแบบการเลือกกลุ่มตัวอย่างแบบเจาะจง ผู้วิจัยคัดเลือกกลุ่มตัวอย่างจำนวน 40 ตัวอย่างจาก 20 บทของนวนิยายข้างหลังภาพ ซึ่งผ่านระดับในการวิเคราะห์ 3 ระดับคือ 1) ระดับเสียงและการสร้างคำ 2) ระดับคำ และ 3) ระดับโครงสร้าง ผลงานวิจัยครั้งนี้พบว่า ในระดับการสร้างคำและการสะกดคำ กลวิธีที่พบมากที่สุดคือ กลวิธีการสร้างคำ ร้อยละ 10.30 กลวิธีที่พบน้อยที่สุดคือ กลวิธีทับศัพท์ ร้อยละ 9.27 ในระดับคำ กลวิธีที่พบมากที่สุดคือ กลวิธีการใช้คำที่มีความหมายเป็นกลาง ร้อยละ 10.30 กลวิธีที่พบน้อยที่สุดคือ กลวิธีการใช้คำยืมหรือคำยืมพร้อมกับคำอธิบาย ร้อยละ 0.51 และ การทดแทนวัฒนธรรม ร้อยละ 0.51 และระดับสุดท้ายคือระดับโครงสร้าง กลวิธีที่พบมากที่สุดคือ กลวิธีการเปลี่ยนวลีเป็นประโยคและเปลี่ยนประโยคเป็นวลี ร้อยละ 17.52 กลวิธีที่พบน้อยที่สุดคือ การถอดความโดยใช้คำที่เกี่ยวข้อง ร้อยละ 0.51 และ กลวิธีการเพิ่มหรือการตัดคำ ร้อยละ 0.51 นอกจากนี้ผลการศึกษาพบว่าเป็นการแปลแบบตรงตัวและแบบเอาความ แสดงให้เห็นถึงปัญหาในการแปลที่สำคัญซึ่งส่วนใหญ่เกิดจากวัฒนธรรมที่ต่างกัน โดยสามารถแก้ไขด้วยกลวิธีการปรับบทแปลที่แตกต่างกันออกไป